Strengthening multi-stakeholder agroecology platforms in Ethiopia: A landscape analysis - Blum, Helen; Tibebe, Degefie; Mockshell, Jonathan; Bergamini, Nadia (2024)
Multi-stakeholder platforms offer a promising approach for sharing agricultural innovation, reducing transaction costs, and catalyzing development by stimulating stakeholder engagement in the innovation process to accelerate food systems transformation. Agriculture-related multi stakeholder platforms (AMSPs) are major players within agricultural development programs’ intervention strategies. However, AMSPs face multiple challenges that limit and negatively impact their functions. This study aims to map the AMSP landscape, examine their operational activities, and provide recommendations for strengthening private- and public-sector engagement to support long-term agricultural sustainability in Ethiopia. The study used a three-step qualitative research approach to identify AMSPs and subsequently collected secondary and primary data. Results reveal five types of AMSPs classified from 29 identified platforms: (i) development organization-led; (ii) civil society organization (CSO)-led; (iii) government-led; (iv) government and development organizations (GDO) co-led; and (v) one private sector-led platform. The AMSPs’ main characteristics were then investigated according to the four basic pillars of organizational theory: structural, contextual, operational, and relational. Next, the study analyzed the influence of each AMSP type on agricultural policies and practices, including those integrating agroecological approaches. The study then examined each AMSP’s achievements and challenges related to AMSP impact and sustainability, together with the constraints related to private- and public-sector engagement, and incentives and investment in agroecological transition. This landscape analysis has identified various mechanisms and possibilities for the Agroecological TRANSITIONS Program — and other related sustainable approaches projects — to engage with the existing AMSPs. This collaboration will stimulate a process for the co-design and co-creation of innovative incentive mechanisms to leverage investment, support the use of holistic traceability tools, and scale out agroecological practices in wheat value chains in Ethiopia.